The determinants of knowledge-based economy development – ICT use in the Silesian enterprises - Ziemba, Ewa; Olszak, Celina M. (Determinanty rozwoju gospodarki opartej na wiedzy – wykorzystanie ICT w śląskich przedsiębiorstwach, 2011)
In the article entitled “The determinants of knowledge-based economy development: the fundamental assumptions” we have described four determinants of knowledge-based economy (KBE) development: education, innovativeness, economic and institutional policies,and ICT (Information Communication Technology). The purpose of this study is an analysis of the ICT use, especially the Internet in the Silesian enterprises, particularly in the context of KBE development. We have analyzed the use of ICT in Silesian enterprises, shown projects that promote the use of ICT in the Silesian enterprises and presented the conclusions based on the conducted research and made recommendations. This paper is addressed to representatives of enterprises, and other players who intend to participate actively in the KBE development by leveraging ICT
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 204-212
Keywords: knowledge-based economy; ICT in enterprises; gospodarka oparta na wiedzy; ICT w przedsiębiorstwach